How commitment to fellow customers affects the customer-firm relationship and customer citizenship behavior. Issue 2 (6th May 2014) - Curth, Susanne; Uhrich, Sebastian; Benkenstein, Martin
Abstract : Purpose: – The purpose of this paper is to analyze how affective commitment to fellow customers influences a customer's affective commitment to the service provider and customer citizenship behavior (CCB). In addition, the paper seeks to examine the moderating role of a customer's calculative commitment to the service organization. Design/methodology/approach: – The study used a large-scale survey among customers of a health club and a scenario-based experiment to test the hypotheses. Findings: – Both empirical studies provide evidence that affective commitment to fellow customers has positive consequences for the customer-firm-relationship. The findings suggest that commitment to fellow customers and commitment to the service organization influence very specific facets of customer citizenship behavior. In addition, the study found preliminary support for the moderating role of calculative commitment. Affective commitment to fellow customers showed the strongest effect on affective commitment to the provider in customer-firm relationships characterized by high (versus low) calculative commitment. Practical implications: – The results of this research have a number of managerial implications. This study suggests measures to strengthen customer-firm-relationships, e.g. generating intensive exchange among customers or attraction of consumer pairs. Providing customers with platforms of valuable relationships to multiplex ties can be a competitive advantage for service providers. Originality/value: – This article is the first that highlights the role of other customers as a target of customer commitment and how this commitment affects both the customer's relationship to the service provider and his or her customer citizenship behavior. The present study therefore broadens our knowledge of how bonding among customers influences consumer behavior in service settings.